The effect of secondary crystallization on crystallization kinetics – Polyethylene terephthalate revisited. (August 2016) - Chen, Ziyu; Hay, James N.; Jenkins, Michael J.
Graphical abstract: Highlights: The Avrami equation has been modified to incorporate secondary crystallization. The presence of secondary crystallization accounts for fractional constant n values. Secondary crystallization develops with the square root of time involving diffusion of small segments of the chain. Primary crystallization involves the linear growth of lamellae with time involving long entangled chain segments. Abstract: The possibility that two concurrent crystallization processes occurring during the crystallization of polymers may account for anomalous fractional values of the Avrami exponent, of no theoretical significance, is reconsidered using data from the recent evaluation of the kinetics of crystallization of poly (ethylene terephthalate) which placed emphasis on evaluating the secondary crystallization stage. In general constant n values in excess of that expected for the crystallization mechanisms could readily be interpreted in terms of the additional crystallinity developed by the secondary process and these values increased commensurate with the rate constant of secondary crystallization. The difference in mechanisms of primary and secondary arises from differences in the mechanism of chain segment diffusion by reptation and the free energies of nucleation of the two growth steps.